Market Management Policy for Enhancing the Local Revenue of Ngaban Village, Sidoarjo Regency: Kebijakan Pengelolaan Pasar untuk Meningkatkan Pendapatan Asli Desa Ngaban Kabupaten Sidoarjo - Herdine Ayu Wulandari; Ilmi Usrotin Choiriyah (Universitas Indo Global Mandiri, 2026)
Purpose : The purpose of this study is to examine the management of Ngaban Village Market in enhancing the Village Original Revenue (PADes), using George R. Terry’s management theory as the analytical framework. Design/methodology/approach : This study employed a qualitative method with a descriptive approach, utilizing observation, interviews, and documentation study through purposive sampling. The data analysis followed the Miles and Huberman model, encompassing the stages of data reduction, data display, and conclusion drawing. Findings : The study reveals that the implementation of Terry’s four management functions—planning, organizing, actuating, and controlling—operates synergistically in the management of the market. Planning is based on market potential and community needs; organizing encompasses task division and resource management; actuating focuses on market operations and public service delivery; and controlling is conducted regularly to ensure target attainment. Practical Implication : The research findings affirm that the integration of the four management functions in a synergistic manner can drive the success of village market management and contribute to the sustainable improvement of community welfare. Originality/value : The findings strengthen Terry’s proposition that management is a coordinated and dynamic process, while also contributing to the advancement of the theory itself.